FRI0230 Tocilizumab in the real clinical practice: a preliminary descriptive analysis from the italian observational trust study. (23rd January 2014) - Fusaro, E.; Tomietto, P.; Colombelli, P.; Abdi-Ali, L.; D'Alessandro, G.; Prandini, P.; Di Matteo, L.; Giacomelli, R.; Martin Martin, L. S.
Abstract : Background: Tocilizumab (TCZ) is a humanised monoclonal antibody that inhibits binding of interleukin-6 (IL-6) to its receptors 1, preventing IL-6–mediated pro-inflammatory activity. TCZ in combination with methotrexate (MTX) is indicated in patients with moderate to severe Rheumatoid Arthritis (RA) with inadequate clinical response or intolerance to one or more DMARDs or TNF-α antagonists. Moreover, TCZ is indicated as monotherapy in patients intolerant to MTX or for whom MTX is considered inappropriate 1 . So far few data are available about the use and clinical impact of TCZ in the real clinical practice . Objectives: Objectives: The primary objective of this multicenter, retrospective and prospective, observational study was to evaluate the percentage of RA patients who achieved low disease activity (DAS28 ≤3.2) and remission (DAS28 <2.6) after 6 months of TCZ treatment. Here are presented the results from a preliminary descriptive analysis conducted on the totality of the enrolled patients, with the aim to describe and compare baseline clinical characteristics of patients treated with TCZ monotherapy versus patients undergoing TCZ combination therapy. Methods: Eligible patients where those with moderate to severe RA who had started TCZ in the 6 months prior to the opening of the center and who were still on treatment at the beginning of the study. Patients were then followed up prospectively to a maximum of 12 months after the first TCZ infusion. Results: One hundred and five (32.6%) patients in the TCZ-monotherapy group and 217 (67.4%) in the TCZ-combination group were enrolled in 58 Italian sites. The two groups were comparable in terms of age, gender, and race. TCZ-mono patients had longer disease duration compared to TCZ-combo (144.9±96.2 months vs 111.9±94.7, respectively). Concerning the pharmacological anamnesis, a greater number of patients assuming TCZ as monotherapy had been previously treated with anti-TNFα (81% vs 67.3% for TCZ mono- and combo therapy respectively) and other non-DMARDs therapies indicated for RA (92.4% vs 80.7%). Baseline clinical characteristics, i.e. DAS28 ≥ 3.2 (94.6% vs 97.4%, for TCZ mono- and combo, respectively) and VAS fatigue (62.8% vs 58.4%), were comparable between groups. Health-related quality of life, HAQ score, was higher in patients treated with TCZ as monotherapy than in those in combination therapy (2.1±3.1 vs 1.5±0.9 respectively). Concerning the pathological anamnesis, no difference was observed between groups, except for a greater number of patients with heart failure, who were treated with TCZ monotherapy. Conclusions: In the real clinical practice, rheumatologists appear more confident in choosing the option of TCZ as monotherapy in patients with (i) longer disease duration, (ii) previous failures to other therapies - especially TNFα inhibitors, (iii) worst quality of life, and (iv) history of heart failure, suggesting that TCZ as monotherapy is considered a valid option in patients intolerant to MTX or for whom MTX is inappropriate. References: Navarro-Millán I et al. Clin Ther. 2012;34:788-802 Disclosure of Interest : None Declared